COMPARISON OF DIFFERENT PCR ASSAYS BASED ON RIBOSOMAL AND OUTER MEMBRANE PROTEIN GENES FOR DIAGNOSIS OF LEPTOSPIROSIS - MADHURIMA DE ROY,; REENA JAIN,; S. NAGENDRA,; U. TUTEJA, (International Journal of Pharma and Bio Sciences, 2014)
Leptospirosis, a disease with protean manifestations, is caused by Leptospira species complex. A definite diagnosis of leptospirosis during the first week of the illness is a major challenge to investigating clinical laboratories. PCR is a rapid, sensitive and specific means of diagnosing Leptospira infections in the early phase of the disease. In this study, the applicability of routine PCR assays targeting ribosomal genes (16S rDNA and 23S rDNA) and outer membrane protein (omp) genes (lipl32, lipl21 and ompl1) were compared for diagnosis of leptospirosis in clinical settings. PCRs based on rDNA were found more robust, specific and detected more number of samples (20 of 310 blood samples of pyrexia of unknown origin cases of human and 5 of 10 urine samples of canine jaundice) than those of omp genes based PCRs. The sensitivity of rDNA PCRs was 10 leptospires/ml of EDTA blood and of omp gene based PCRs was 103 leptospires/ml. Further comparative analysis of these PCRs was undertaken with culture. All the samples found positive by rDNA PCRs yielded the growth of leptospires following inoculation in EMJH media. So, 16S and 23S rDNA PCRs as compare to omp gene based PCR were found to be the most suitable for diagnosis of leptospirosis.